Formulation of a Semisolid Emulsion Containing Leptospermum scoparium Essential Oil and Evaluation of In Vitro Antimicrobial and Antibiofilm Efficacy - Porter, Gemma C.; Safii, Syarida H.; Medlicott, Natalie J.; Duncan, Warwick J.; Tompkins, Geoffrey R.; Coates, Dawn E. (Planta Medica, 2021)
Manuka oil, an essential oil derived from the Leptospermum scoparium, has been traditionally used for wound care and as a topical antibacterial, antifungal, and anti-inflammatory. However, the essential oil is not well retained at mucosal sites, such as the oral cavity, where the benefits of the aforementioned properties could be utilized toward the treatment of persistent biofilms. Within this study, L. scoparium essential oil was incorporated into a semisolid emulsion for improved delivery. The safety profile of L. scoparium essential oil on human gingival fibroblasts was determined via cell viability, cytotoxicity, and caspase activation. The minimal bactericidal concentration of L. scoparium essential oil was determined, and the emulsionʼs antibiofilm effects visualized using confocal laser scanning microscopy. L. scoparium essential oil demonstrated a lower IC50 (0.02% at 48 h) when compared to the clinical control chlorhexidine (0.002% at 48 h) and displayed lower cumulative cytotoxicity. Higher concentrations of L. scoparium essential oil (≥ 0.1%) at 6 h resulted in higher caspase 3/7 activation, suggesting an apoptotic pathway of cell death. A minimal bactericidal concentration of 0.1% w/w was observed for 6 oral bacteria and 0.01% w/v for Porphyromonas gingivalis. Textural and rheometric analysis indicated increased stability of emulsion with a 1 : 3 ratio of L. scoparium essential oil: Oryza sativa carrier oil. The optimized 5% w/w L. scoparium essential oil emulsion showed increased bactericidal penetrative effects on Streptococci gordonii biofilms compared to oil alone and to chlorhexidine controls. This study has demonstrated the safety, formulation, and antimicrobial activity of L. scoparium essential oil emulsion for potential antibacterial applications at mucosal sites.
Keywords: Myrtaceae; Leptospermum Scoparium; essential oil; antimicrobial; emulsion; periodontal disease